Kajian Penerimaan Aplikasi IKD Dalam Meningkatkan Kualitas Layanan Dukcapil Pemalang: Upaya Menuju Transformasi Layanan - Pangesti, Dias Annisaa; Nugraha, Joko Tri; Sinuraya, Suci Iriani; Akhni, Ghaziah Nurika (Jurnal Ilmiah Global Education, 2024)
E-government was driven successfully due to government initiatives and acceptance of technology. This research aims to test whether perceived usefulness, ease of use, and security have a positive relationship with user interest in Digital Population Identity (IKD) in Pemalang Regency. The quantitative method is the method used in this research with a sample of 100 people who use Digital Population Identity (IKD). The results obtained from this research show that there is a very strong positive and significant relationship between perceived usefulness, user-friendliness, and security on user interest in IKD. Results were obtained with a significance level of 0.05, namely, r calculated 0.951 > r table 0.195. Apart from that, obtaining a sig value of 0.000 < 0.05 indicates that the alternative hypothesis (Ha) is accepted so that the null hypothesis (Ho) is rejected. This means that the degree of relationship between the variables of perceived usefulness, user convenience, and security on user interest is a very strong correlation category.